Periosteal Chondrosarcoma Presenting as a Cystic Lesion – A Rare Case Report - Mangesh Londhe; Ranjana Roy; Sushama Gurwale; Shirish Chandanwale (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
Periosteal chondrosarcoma is a rare malignant cartilaginous tumor originating on the bone surface in close association with the periosteum. It predominantly affects the metaphysis of long tubular bones. It is a rare subtype of chondrosarcoma representing about 2.5% of all chondrosarcomas. It usually presents as a large lobulated mass of size greater than 5 cm. However, cystic presentation is extremely rare. Hence, we report this rare case of multilocular cystic lesion of the lower end of femur, appearing benign radiologically and diagnosed as periosteal chondrosarcoma on histopathology.